Globalisation and Gender-Based Inequality in the Ondo State Local Government Service Commission’s Recruitment Process: Globalisation and Gender - Arowolo, Dare Ezekiel (JISR management and social sciences & economics, 2024)
At the centre of societal development is a virile and efficient public service. Also, efficiency of any work place largely depends on the quality of its personnel. Recruitment and selection are vital tools in hiring the right people. However, recruitment and selection exercises in the civil service seem to be susceptible to the forces of globalisation, and as such, raise a question of gender inequalities. As sufficient as literature on recruitment and selection in the Nigerian civil service has been, there is a dearth of literature linking gender inequality in the recruitment process at the Ondo State Local Government Service Commission (OSLGSC) to globalisation. Using survey and evidence-based research method, this study therefore examines the extent to which globalisation widens the existing gender inequality in the recruitment process at the OSLGSC. The study finds evidence that globalisation significantly skewed recruitment process towards men. It therefore concludes that gender consideration determines appointments into the OSLGSC.